In vitro and in vivo studies of Dragon's blood plant (D. cinnabari)-loaded electrospun chitosan/PCL nanofibers: Cytotoxicity, antibacterial, and wound healing activities - Irani, Mohammad; Abadi, Parvaneh GhaderiShikhi; Ahmadian-Attari, Mohammad Mahdi; Rezaee, Aryan; Kordbacheh, Hananeh; Goleij, Pouya (Elsevier, 2024)
The D. cinnabari plant was loaded into the chitosan (Chn)/polycaprolactone (PCL) nanofibers in two forms: resin (D. cinnabari) and its ethyl acetate fraction. The Chn/PCL, Chn/PCL/D. cinnabari (CPD, 1, 3, and 5 %), and Chn/ PCL/ethyl acetate extract D. cinnabari (CPED, 1, 3, and 5 %) showed no toxicity against human dermal fibroblast cells. The lactate dehydrogenase assay results indicated that the toxicity of pour, coated D. cinnabari, and CPED nanofibers were lower than 10 and 15 % after 1 and 3 days, respectively. The antibacterial results showed the inhibition zone for ethyl acetate extract D. cinnabari (ED-3 %), the Chn/PCL-2, and CPED3% nanofibers was 8.1, 7.4, 4.2, 5.1 mm, 12.8, 12.4, 21.7, 17.2 mm, and 24.7, 22.9, 37.1, 30.2 mm against S. aureus, B. subtilis, E. coli, and P. aeruginosa, respectively. The antibacterial activity results showed synergistic effect between the Chn/PCL and ethyl acetate extract D. cinnabari occurred. The diameter of wounds (1.50 x 1.50 cm diameter) made on the dorsal surface of rabbits reduced to 1.50 x 0.70, 0.50 x 0.30, 1.00 x 1.00, 0.60 x 0.50, 0.20 x 0.05, and 0.00 x 0.00 cm in the presence of ordinary gauze dressing, silver sulfadiazine, ED-3 %, Chn/PCL-2, CPD3%, and CPED3%nanofibers, respectively, after 14 days.
Keywords: D. cinnabari -loaded chitosan nanofibers; Antibacterial activity; Wound healing